JOSÉ MARTÍ AS EDUCATOR: PROMOTION OF SELF – TEACHING IN CHILDREN AND YOUNG PEOPLE - Martínez González, Luis Ernesto (Atenas, 2012)
Within the concept of education of José Martí on self-education took center. In his writings on education and all of his work shows the importance attached to learning itself, which is also reflected in their practical work as an educator. This was expressed clearly in their pedagogical influence on several children and young people with whom was associated throughout his life. This article seeks to reveal the educational significance to the promotion of self-education had on children and youth by the Apostle of the independence of Cuba.